Penerapan Model Problem Based Learning dalam Pembelajaran PAI untuk Meningkatkan Kemampuan Berpikir Kritis Siswa: Penelitian - Siti Fahra Utami; Amanda Ikra Negara; Wulan Anggraini; Rita Novita Sari; Mardiah Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in Islamic Religious Education (IRE) and analyze its contribution to enhancing students' critical thinking skills at the Madrasah Ibtidaiyah level. This research employs a descriptive qualitative approach, with the subjects consisting of an IRE teacher and fifth-grade students at MI Al-Hikmah, South Sumatra. Data were collected through observation, interviews, and documentation, and then analyzed thematically. The research findings indicate that the implementation of the Problem Based Learning (PBL) model effectively increases student engagement and participation in the learning process. Students become more reflective, critical, and collaborative when faced with issues related to religious values and daily life. The teacher observed positive changes in class dynamics, including improvements in students' ability to analyze problems, develop arguments, and formulate rational and Islamic solutions. However, some challenges were also identified, such as the limited time for learning and the varying levels of critical thinking ability among students. Overall, this study concludes that the Problem Based Learning (PBL) model is effective in enhancing students' critical thinking skills in IRE learning. Problem Based Learning (PBL) provides a contextual, innovative, and religious approach, which helps develop a critical Islamic thinking character from an early age. Therefore, this model can serve as an effective alternative teaching strategy in Islamic religious education at the Madrasah Ibtidaiyah level.